ASUHAN KEPERAWATAN PADA Tn.H DENGAN CKD (Chronic Kidney Disease) YANG MENJALANI TERAPI HEMODIALISA DI RUANGAN PEJUANG RSUD BANGKINANG TAHUN 2025 - Febriyanti, Iin; Indrawati (Jurnal Spektrum Kesehatan Indonesia, 2025)
Chronic Kidney Disease (CKD) is a progressive and irreversible impairment of kidney function that seriously affects the patient’s quality of life and requires hemodialysis therapy as a substitute for kidney function. This study aims to describe the implementation of nursing care for patients with CKD undergoing hemodialysis therapy, with a case study on Mr. H at Bangkinang Regional General Hospital. The design used is a descriptive case study with a nursing process approach. The assessment results showed main complaints including shortness of breath, back pain, sleep disturbances, and decreased appetite. The established nursing diagnoses include ineffective breathing pattern, acute pain, sleep pattern disturbance. After three days of intervention, gradual improvement in the patient’s condition was observed. The conclusion of this study shows that structured and continuous nursing care plays an important role in improving the condition and quality of life of patients with CKD. It is recommended that nurses continue to enhance education, monitoring, and holistic support for patients and their families